2011
DOI: 10.1016/j.juro.2011.02.2698
|View full text |Cite
|
Sign up to set email alerts
|

Incontinence After Radical Prostatectomy: A Patient Centered Analysis and Implications for Preoperative Counseling

Abstract: Despite patient concerns of incontinence after prostatectomy they report little interference with quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 16 publications
3
22
0
5
Order By: Relevance
“…5 It is reported that approximately 4-22% of patients do not achieve urinary continence 12 months after RARP. 4,[6][7][8][9] Recent studies reported that preoperative clinical factors, anatomical characteristics, and surgical techniques are significantly associated with urinary incontinence after RARP. 1,7,[10][11][12][13][14][15] Of these factors, membranous urethral length (MUL) is an important factor that directly correlates with the functional sphincter mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…5 It is reported that approximately 4-22% of patients do not achieve urinary continence 12 months after RARP. 4,[6][7][8][9] Recent studies reported that preoperative clinical factors, anatomical characteristics, and surgical techniques are significantly associated with urinary incontinence after RARP. 1,7,[10][11][12][13][14][15] Of these factors, membranous urethral length (MUL) is an important factor that directly correlates with the functional sphincter mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Wang & Eriksson, 2014) e trinta e três estudos observacionais (Anderson et al, 2012;Bach et al, 2011;Berge et al, 2013;Bradford et al, 2010;Choi et al, 2011;Dahl et al, 2014;Froehner et al, 2012;Geraerts et al, 2013;Guilger et al, 2011;Hartz et al, 2013;Holm et al, 2013;Inoue et al, 2009;Kimura et al, 2011;Koehler et al, 2012;Ku et al, 2009;Lee et al, 2012;Lin et al, 2012;Martin et al, 2011;Namiki et al, 2012;Namiki et al, 2009;Nyarangi-Dix et al, 2013;Parker et al, 2011;Pfalzgraf et al, 2014;Santa Mina et al, 2014;Santa Mina et al, 2010;Thompson et al, 2014;Thornton et al, 2012;Treiyer et al, 2011;van der Poel et al, 2013;R. Wang et al, 2012;Willis et al, 2012).…”
Section: Características E Resultados Dos Estudos Incluídosunclassified
“…Outros nove estudos (Choi et al, 2011;Froehner et al, 2012;Geraerts et al, 2013;Holm et al, 2013;Martin et al, 2011;Santa Mina et al, 2014;Santa Mina et al, 2010;R. Wang et al, 2012) foram agrupados na categoria Ênfase no domínio urinário, apresentando-se como a segunda categoria com o maior número de estudos.…”
Section: Características E Resultados Dos Estudos Incluídosunclassified
See 2 more Smart Citations